A Bout of High Intensity Interval Training Lengthened Nerve Conduction Latency to the Non-exercised Affected Limb in Chronic Stroke - Abraha, Beraki; Chaves, Arthur R.; Kelly, Liam P.; Wallack, Elizabeth M.; Wadden, Katie P.; McCarthy, Jason; Ploughman, Michelle (Frontiers in Physiology, 2018)
Objective: Evaluate intensity-dependent effects of a single bout of high intensity interval training (HIIT) compared to moderate intensity constant-load exercise (MICE) on corticospinal excitability (CSE) and effects on upper limb performance in chronic stroke. Design: Randomized cross-over trial. Setting: Research laboratory in a tertiary rehabilitation hospital. Participants: Convenience sample of 12 chronic stroke survivors. Outcome measures: Bilateral CSE measures of intracortical inhibition and facilitation, motor thresholds, and motor evoked potential (MEP) latency using transcranial magnetic stimulation. Upper limb functional measures of dexterity (Box and Blocks Test) and strength (pinch and grip strength). Results: Twelve (10 males; 62.50 ± 9.0 years old) chronic stroke (26.70 ± 23.0 months) survivors with moderate level of residual impairment participated. MEP latency from the ipsilesional hemisphere was lengthened after HIIT (pre: 24.27 ± 1.8ms, and post: 25.04 ± 1.8ms, p=0.01) but not MICE (pre: 25.49 ± 1.10ms, and post: 25.28 ± 1.0ms, p=0.44). There were no significant changes in motor thresholds, intracortical inhibition or facilitation. Pinch strength of the affected hand decreased after MICE (pre: 8.96 ± 1.9kg vs post: 8.40 ± 2.0kg, p=0.02) but not after HIIT (pre: 8.83 ± 2.0kg vs post: 8.65 ± 2.2kg, p=0.29). Regardless of type of aerobic exercise, higher total energy expenditure was associated with greater increases in pinch strength in the affected hand after exercise (R2=0.31, p=0.04) and decreases in pinch strength of the less affected hand (R2=0.26 p=0.02). Conclusion: A single bout of HIIT resulted in lengthened nerve conduction latency in the affected hand that was not engaged in the exercise. Longer latency could be related to the cross-over effects of fatiguing exercise or to reduced hand spasticity. Somewhat counterintuitively, pinch strength of the affected hand decreased after MICE but not HIIT. Regardless of the structure of exercise, higher energy expended was associated with pinch strength gains in the affected hand and strength losses in the less affected hand. Since aerobic exercise has acute effects on MEP latency and hand strength, it could be paired with upper limb training to potentiate beneficial effects.